Tribological and performance assessment of two wheeler brake pads using dynamometer testing - P. Baskar; Keshav Shukla (Scientific Reports, 2025)
Abstract Braking systems are critical for vehicle safety, with brake pads influencing performance, durability, and environmental impact. This study compares organic and sintered brake pads, analyzing tribological properties, thermal stability, and wear resistance. Organic pads, made from synthetic fibers and resins, offer low noise and environmental benefits but degrade faster under heat. Sintered pads, composed of fused powdered metals, exhibit superior heat resistance, durability, and braking consistency under extreme conditions. Testing included dynamometer evaluations, measuring stopping distance, deceleration, braking pressure, and temperature variations. Sintered pads maintained a stable coefficient of friction, lower stopping distances, and consistent deceleration over time, requiring less hydraulic pressure for equivalent braking force. Organic pads wore faster and showed increased stopping times. The findings highlight sintered pads as ideal for high-performance applications, while organic pads remain suitable for cost-sensitive, noise-conscious environments, contributing to advancements in automotive safety and sustainable braking solutions.